Bridging Dysplasia to Diagnostic Oral Pathology: Comparative Evaluation of Leukoplakia as a Predictor of Oral Malignancy - Amna Sarfaraz; Mariam Fatima; Sahd Rashid; Saba Ejaz; Ayesha Siddiqa; Aiza Khan; Kainat Zafar (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Oral leukoplakia is a frequently encountered premalignancy and potential source of oral dysplastic change, with the probable clinical manifestation in the form of an oral leukoplakia lesion. In this study, the authors endeavor to carry out the histological grading of dysplasia in leukoplakia and the relationship between the grades of dysplasia and malignant transformation.